Effectiveness of the Solid Waste Management in Bangkok Metropolitan Administration - Patanaporn, Anusorn (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The purpose of this study was to find out factors impinging upon the effectiveness of the solid waste management carried out by Bangkok Metropolitan Administration whose end result was to make it more efficient. Mixed method was used for data gathering from respondents composed of 10 persons for indent interview for qualitative purpose while 400 sets of questionnaire used wailed to the respondents for quantitative purpose ; out of which 350 had returned the questionnaire. The data were then audited for their reliability based on documents, books and researches understating before rail into view the target groups, observation based on descriptive method. It was found from the study that factors impinging upon effectiveness and efficiency of the above solid waste management using KPI were as follows : (1) there exist the KPI’s for effectiveness, (2) These exist clear principles and practicable, including diversity of management and plan at the levels of policy, plan, strategy, project/activities of Bangkok Metropolitan Administration ; (3) These exist leadership and will/orienteers of the BMA’s leaders aimed at fostering and evolving solid wastes to make Bangkok to be clean in the years to come which, in turn, being the most important for effective and sustained solid waste management ; (4) there exist KPI’s assigning for measuring the effectiveness in terms of quantity, quality and frequency of work operation with main principles of personnel attached to teach. District of BMA. In addition two more factors contributing to the success of solid waste management-Man and Money to motivate the BMA’s personnel work toward its objectives via research and development and design, including foreign innovation on appropriate solid waste management with systematic and preventive measures toward resolving the environmental problems of the people in the years to come. Article history : Accepted 21 April 2017 SIMILARITY INDEX = 0.00